Identification of Zr(iv)-based architectures generated from ligands incorporating the 2, 2′-biphenolato unit. Issue 19 (12th April 2016) - Miao, Chengrui; Khalil, Georges; Chaumont, Alain; Mobian, Pierre; Henry, Marc
Abstract : The architectures generated from 2, 2′-biphenol-based proligands and the Zr(iv ) centre are identified. The triple-stranded helicate formed in solution contrasts strongly with the helical complex characterised in the solid-state. Abstract : The structural identification in solution of the Zr(iv ) complexes involving two 2, 2-biphenol-based proligands is reported. The proligand L 1 H2 contains one 2, 2-biphenol unit whereas L 2 H4 incorporates two 2, 2-biphenol units linked by a para -phenylene bridge. Diffusion Ordered Spectroscopy (DOSY) combined with electrospray mass spectrometry analysis and density functional theory (DFT) allowed for determining the molecular structures of such Zr(iv )-based architectures. It is proposed that [Zr(OPr i )4 (HOPr i )] in the presence of L 1 H2 generates an octahedral complex formulated as [ZrL 1 3 H2 ]. Concerning the self-assembled architecture incorporating the L 2 ligand, the analytical data highlight the formation of an unprecedented neutral Zr(iv ) triple-stranded helicate ([Zr2 L 2 3 H4 ]). Insight into the geometry of these complexes is obtained via DFT calculations. Remarkably, the helicate structure characterized in solution strongly contrasts with the triple-stranded structure of the complex that crystallizes.